In vitro Antioxidant, Antimicrobial and Antiprotozoal Activities of Ethanolic Extract and its Various Fractions from Asphodelus fistulosus Seeds - Alam, Mohammad Mahboob; Al-Fahad, Ahmed Jaman; Nazreen, Syed (Asian Journal of Biological and Life Sciences, 2018)
Asphodelus fistulosus (Asphodelaceae) has been traditionally used in the treatment of fungal and dermatomucosal infections. The present study aims to evaluate the antioxidant, antimicrobial and antiprotozoal activities of the ethanolic extract and its various fractions of seeds of the plant. The results of antioxidant study indicated that A. fistulosus contain polyphenols, proving them to be perfect sources of antioxidants. The plant showed significant antimicrobial and antiprotozoal activities. The metabolites, anthraquinones, flavonoids, terpenes and phenolic acids could be responsible for such activity of this plant. The results of the present study of Asphodelus fistulosus supported its traditional use for the treatment of fungal and dermatomucosal infections. Key words: Asphodelus fistulosus, Antiprotozoal, Antimicrobial, Antioxidant.
Keywords: Antimicrobial; Antioxidant; Antiprotozoal; Asphodelus fistulosus; Total phenolic content